2017
DOI: 10.1007/s10548-017-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Intracranial EEG-fMRI Shows Inter-Modality Correlation in Time-Resolved Connectivity Within Normal Areas but Not Within Epileptic Regions

Abstract: For the first time in research in humans, we used simultaneous icEEG-fMRI to examine the link between connectivity in haemodynamic signals during the resting-state (rs) and connectivity derived from electrophysiological activity in terms of the inter-modal connectivity correlation (IMCC). We quantified IMCC in nine patients with drug-resistant epilepsy (i) within brain networks in 'healthy' non-involved cortical zones (NIZ) and (ii) within brain networks involved in generating seizures and interictal spikes (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 86 publications
2
43
0
Order By: Relevance
“…Beyond the signal-to-noise limitations in human concurrent EEG-fMRI, there is evidence that γ-and β-band connectivity may contain information complementary to fMRI-derived connectivity. A weaker relation to fMRI connectivity has been reported for β and low-γ compared to other bands in intracranial electrophysiological recordings in humans (38,58) and in animals (59,60). The weaker relationship for β-and low γ-bands likely reflects a general property of the electrophysiology-fMRI relationship.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 82%
“…Beyond the signal-to-noise limitations in human concurrent EEG-fMRI, there is evidence that γ-and β-band connectivity may contain information complementary to fMRI-derived connectivity. A weaker relation to fMRI connectivity has been reported for β and low-γ compared to other bands in intracranial electrophysiological recordings in humans (38,58) and in animals (59,60). The weaker relationship for β-and low γ-bands likely reflects a general property of the electrophysiology-fMRI relationship.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 82%
“…Moreover, the same patients explored by stereotactic-EEG and functional MRI (at different times) exhibit increased functional connectivity in stereotactic-EEG but decreased functional connectivity using BOLD signals within epileptic structures (Bettus et al, 2011). A recent study confirmed this discrepancy in simultaneous recordings of functional MRI and stereotactic-EEG, demonstrating that intermodal connectivity correlation exists in non-epileptic structures but is altered in the epileptic zones (Ridley et al, 2017). Thus, whereas increased EEG connectivity could be related to pathologically reinforced links between hyperexcitable structures, decreased functional MRI connectivity could be more likely related to metabolic/perfusion alterations (Bettus et al, 2009).…”
Section: Comparison With Mri Datamentioning
confidence: 90%
“…Nevertheless, despite numerous studies on the subject, network organization in epilepsy remains incompletely understood (Richardson, 2012;Bernhardt et al, 2013;Duncan et al, 2016; Bartolomei et al, 2017). A large majority of literature has focused on MRI extracted connectivity (Bernhardt et al, 2013;Duncan et al, 2016) although the relationship between functional MRI and electrophysiological data is still incompletely understood (Bénar et al, 2006;Bettus et al, 2011;Coan et al, 2016;Ridley et al, 2017). Other studies used electrophysiological recordings (intracranial or not) to compute functional connectivity (Kramer et al, 2011;Chu et al, 2012;Kramer and Cash, 2012;van Diessen et al, 2013;Yaffe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spikes were detected automatically with a spike detection algorithm (Amadeus software) during the selected parts of wakefulness and NREM sleep in each bipolar derivation. An experienced neurophysiologist then checked automatically detected spikes to corroborate them or not (Figure ).…”
Section: Methodsmentioning
confidence: 99%